Computed Tomographic Study on the Prevalence of the Onodi Cell - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:The prevalence of the Onodi cell varies in different populations. Its involvement in sinus pathology is characterized by varied clinical symptoms due to its proximity to the internal carotid artery and optic nerve. Endoscopic surgical management of sinus pathologies poses a great risk of injury to these neurovascular structures.Aim:This study elucidates the prevalence of the Onodi cell in a Nigerian Teaching Hospital.Setting and Design:This was a retrospective cross-sectional study conducted in the Radiology unit of a Teaching Hospital in Nigeria.Materials and Methods:Brain computed tomography (CT) images of 336 patients aged ≥20 years were evaluated for the presence of the Onodi cell. The study was approved by the institution before accessing the digital images. The age and gender of patients and the presence and location of the Onodi cell were recorded.Statistical Analysis Used:Data were entered in Statistical Package for Social Sciences version 23 for analysis of prevalence and subsequent comparisons using the Chi-square test. The significance level was considered atP< 0.05.Results:The prevalence of Onodi cell was 16.4% and was only observed unilaterally with a slightly lower frequency on the right (27, 8.0%) than the left (28, 8.3%). The prevalence did not show any significant side or gender differences (P> 0.05).Conclusion:The Onodi cell was present in the studied population, thus highlighting the need for their preoperative recognition on CT to abate iatrogenic complications during endoscopic surgeries.